PPARβ/δ Agonist GW501516 Inhibits Tumorigenicity of Undifferentiated Nasopharyngeal Carcinoma in C666-1 Cells by Promoting Apoptosis - Ji, Yangyang; Li, Hui; Wang, Fang; Gu, Linglan (Frontiers in Pharmacology, 2018)
Activation of peroxisome proliferator-activated receptor β/δ (PPARβ/δ) had been linked to inhibition on the proliferation and apoptosis in a few cancer cell lines. However, limited data exists regarding the role of PPARβ/δ in nasopharyngeal carcinoma (NPC). This study was undertaken to determine the effect of PPARβ/δ on cell proliferation, anchorage-dependent clonogenicity, and ectopic xenografts in the human NPC cell lines. Gene and protein expression of PPARβ/δ were reduced specifically in the poor- and un-differentiated NPC cell lines as compared with the control NP-69 cells. Ligand activation of PPARβ/δ by GW501516, a specific PPARβ/δ selective agonist, inhibited cell proliferation and colony formation strikingly, and induced a G2/M phase arrest in the EBV positive undifferentiated NPC C666-1 cells relative to the control cells. Moreover, GW501516 induced C666-1 cell apoptosis in a caspase and BAX dependent manner. In accordance with the in-vitro result, GW501516 significantly suppressed the ectopic NPC xenograft tumorigenicity that derived from the C666-1 NPC cells in BALB/c nu/nu mice. This effect is greatly associated with its inhibition on the gene and protein expression of integrin-linked kinase (ILK) through activation of the AMPKα-dependent signaling pathways. Collectively, we showed that PPARβ/δ expression is in reverse correlation with the degree of differentiation in the NPC cell lines, and revealed the anti-tumorigenic effects of GW501516 in NPC cells by activation of AMPKα. This study suggested that PPARβ/δ targeting molecules may be useful for the poor-, and particularly un-differentiated NPC chemoprevention.